USE OF DUAL AND TRIPLE INCRETIN AGONISTS (TIRZEPATIDE AND RETATRUTIDE) IN THE TREATMENT OF OBESITY AND TYPE 2 DIABETES MELLITUS - Gabriel, Felipe Veiga Kezam; Cruz, Marilda Lopes; Soster, Tamires; Soares, Antonio Matheus Melo; Neglisoli, Vanessa; Delfino, Otávio de Meireles; Marinho, Marcella de Fátima Lomeu; Bombardelli, Laura Lappe; Cruz, Gabriele Longo; Viana, Valéria Goulart; Neri, Diegomaier Nunes; Dezan, Mateus Souza; et al. (Seven Editora, 2026)
Obesity and type 2 diabetes mellitus (T2DM) represent major global public health challenges, requiring more effective and integrated therapeutic strategies. In this context, dual and triple incretin agonists have emerged as innovative approaches by targeting multiple metabolic pathways simultaneously. This study aimed to provide a critical and comparative analysis of tirzepatide and retatrutide in the treatment of obesity and T2DM, based on recent scientific evidence. This narrative critical-analytical review was conducted through a structured search in PubMed/MEDLINE, Scopus, Web of Science, ScienceDirect, and Cochrane Library, including studies published between 2016 and 2025. A total of 20 studies were included, comprising clinical trials, systematic reviews, meta-analyses, and narrative reviews. The findings indicate that tirzepatide demonstrates well-established efficacy in glycemic control and weight reduction, whereas retatrutide shows greater potential for weight loss, likely related to increased energy expenditure mediated by glucagon receptor activation. However, this apparent superiority is accompanied by a higher incidence of adverse events and limited long-term evidence. The lack of direct head-to-head clinical trials and methodological heterogeneity across studies limit definitive conclusions regarding their comparative effectiveness. Therefore, although dual and triple incretin agonists represent a significant advancement in the management of obesity and T2DM, further long-term and head-to-head comparative studies are required to define their role in clinical practice.